KEDISIPLINAN PEGAWAI DALAM PELAYANAN PUBLIK DI KANTOR CAMAT LONG IKIS KABUPATEN PASER PROVINSI KALIMANTAN TIMUR TAHUN 2016 - Ranggi Yuska Pratiwi; Ali Yusri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Public service is basically an effort carried out by a person, group or bureaucracy to provide assistance and facilities to the community in achieving a certain goal. The purpose of a public service in general is to be able to satisfy the public regardless of anything. The background of this research is that the staff of the Long Ikis Sub-District Office in public services lacked discipline so that the services provided at the Camat's Office were not optimal. The formulation of the problem from this research is How is the application of employee discipline in public services at the Office of the Long Ikis Sub-District of Paser Regency, East Kalimantan in 2016?This study aims to determine the application of employee discipline in public services at the Office of the Long Ikis Sub-District of Paser Regency, East Kalimantan Province in 2016 and to find out the causes of indiscipline in public services at the Office of the Long Ikis Sub-District in East Kalimantan Paser Regency in 2016. This study uses qualitative with descriptive research types. Data collection techniques used were interviews and documentation. Data analysis was carried out in a descriptive manner on the Discipline of Employees in Public Service in the Office of the Long Ikis District Head of 2016 obtained from written documents and interviews.The results showed that the discipline of employees in public service at the Long Ikis Sub-District Office in 2016 had not run optimally, this was seen from several problems such as time discipline, task discipline and behavioral discipline. The reasons for the low discipline of employees in public services at the Office of the Long Ikis Sub-District of Paser Regency in East Kalimantan in 2016 are due to goals and abilities, role models, inherent supervision, legal sanctions and firmness. Keywords: Local Government, Public Service, Discipline